The intervention project to improve physical fitness for Tokyo 2020 Olympic Game of Japanese sailing team - Hagiwara, M.; Nakamura, M.; Saito, T.; Nakamura, K. (Journal of High Performance Sport, 2021)
The purpose of this case study was to demonstrate whether the intervention project implemented by the support team for the 2020 Tokyo Olympic Games led to an improvement in the physical fitness of the Japanese national sailing team. Support team was established in collaboration between the Japan Sailing Federation and the Japan Institute of Sport Sciences. The support team conducted the intervention project by creating fitness assessment indicators and targets, conducting fitness checks and workshops, and providing training instruction. As a result of physical fitness check, the increase in lean body mass and improvement in anaerobic and aerobic fitness performance were observed after the intervention project. On the other hand, the improvement in physiological indicators of maximal and supramaximal exercise level was not observed and individual issues of athletes were found. These results suggested that the intervention project and the results of the physical fitness check presented in this case study can be useful indicators for the future development and strengthening of sailing athletes in Japan.